2020
DOI: 10.21776/ub.jam.2020.018.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Is the Loyalty Program Effective in Creating Loyalty Program Satisfaction and Store Loyalty? An Evidence From Indonesia Retail Industry

Abstract: Retailers must find specific ways to be able to continue to maintain their business with changes in consumer behavior. Some retailers use a loyalty program as their marketing strategy that provides certain additional benefits for frequent consumers. The objective of this work is to verify the effect of the loyalty program and loyalty program satisfaction on store loyalty. The data was collected through questionnaires from 150 respondents. The results reflected that loyalty programs significantly influence loya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Loyalitas konsumen adalah kemungkinan pelanggan untuk membeli barang lagi dan keinginan mereka untuk tetap setia sehingga menjadi mitra bisnis. Konsumen yang setia akan berbicara baik kepada orang lain, mendorong orang lain untuk bertransaksi, dan menjadi pembeli pertama di masa depan (Hendrawan & Anggraeni, 2020). Tjiptono (2014) berpendapat ada lima penilaian untuk menilai loyalitas konsumen, antara lain pembelian ulang, rasa suka yang besar pada merek, ketetapan pada merek, keyakinan bahwa merek tertentu merek terbaik, dan rekomendasi merek.…”
Section: Loyalitas Konsumen Produk Lokal Kecantikanunclassified
“…Loyalitas konsumen adalah kemungkinan pelanggan untuk membeli barang lagi dan keinginan mereka untuk tetap setia sehingga menjadi mitra bisnis. Konsumen yang setia akan berbicara baik kepada orang lain, mendorong orang lain untuk bertransaksi, dan menjadi pembeli pertama di masa depan (Hendrawan & Anggraeni, 2020). Tjiptono (2014) berpendapat ada lima penilaian untuk menilai loyalitas konsumen, antara lain pembelian ulang, rasa suka yang besar pada merek, ketetapan pada merek, keyakinan bahwa merek tertentu merek terbaik, dan rekomendasi merek.…”
Section: Loyalitas Konsumen Produk Lokal Kecantikanunclassified
“…Program satisfaction (PS) is a measure of how a specific program established by a company meet or surpass their audience's expectation (Vesel & Zabkar, 2009). According to (Hendrawan & Anggraeni, 2020), PS can be measured through "the number of customers, or percentage of total customers, whose reported experience with a firm's program, its products, or its services (ratings) exceeds specified satisfaction goals". In the context of food retail industry, a study from (Demoulin & Zidda, 2008) found that customers are tend not have sensibility in terms of product price when the loyalty program reward is fulfilling their expectations.…”
Section: Relationship Between Program Satisfaction Program Loyalty An...mentioning
confidence: 99%
“…Loyal customer is an essential factor in company's sustainability (Berezan et al, 2015;Han & Ryu, 2009;Hendrawan & Anggraeni, 2020;Jang & Mattila, 2005;Mimouni-Chaabane & Volle, 2010;Pratika & Sutikno, 2017;Robinson, 2013;Sharp & Sharp, 1997). For that reason many companies are using various approaches in order to win the market by maximizing customer "Stickiness" to the brand (Drèze & Hoch, 1998;Steyn et al, 2010;Suh & Yi, 2012).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Meyer-Waarden (2008) also declares that loyalty programmes influence the purchasing behaviour of customers where a significant difference is displayed by members who contribute to loyalty programmes over non-members in terms of their purchasing behaviour. Hendrawan and Anggraeni (2020) declare that loyalty programmes significantly influence customer satisfaction. Koo et al (2020) state that the perceived value of loyalty programmes has a significant impact on customer satisfaction.…”
Section: Loyalty Programmesmentioning
confidence: 99%